EVALUATION ON THE EFFECT OF ANTIRETROVIRAL DRUGS ON CD4 T-CELL AND THE INCREMENT OF BODY WEIGHT AMONG HIV-AIDS PATIENTS IN SURABAYA - Frederika, Edith; Normalina, Irine; Nasronudin, Nasronudin; Mega, Rury (Indonesian Journal of Tropical and Infectious Disease, 2012)
Antiretroviral drug discovery has encouraged a revolution in the care of people living with HIV, although it has not been able to cure diseases and to increase the challenge in terms of drug side effects. Side effects of antiretroviral drugs are fairly common occurrences in HIV patients and generally occurr within the first three months after initiation of antiretroviral therapy, although long-term side effects are also often found afterwards. This study aims to evaluate the number of CD4 T-cells in patients with AIDS before and after getting on ARV therapy, the side effects arising during the taking of ARVs are related to the increment of body weight among the HIVAIDS patients. Subjects were then narrowed down from 25 to 12 due to the incomplete data. The results showed that the top three most side effects which often occur in people with AIDS are appetite loss (20.0%), nausea (17.8%), and diarrhoea (15.6%). Meanwhile, about 58% of the subjects experienced increment of their body weight, and 42% were losing weight due to the side effects of the ARV therapy. Among those who lost their body weight, 50% were in the productive ages between 21–30 years old. The present study shows that combination antiretroviral therapy gives good results to the increased number of CD4 T-cells in patients living with HIV, as shown by the tendency of an increment in the number of CD4 T-cells in patients who received antiretroviral therapy. However, around 42% of those patients were losing weight because of the side effects of the therapy. Therefore, the importance of giving specific nutrient to overcome with the weight loss is needed to be given to the patients HIV instead of only giving the ARV treatment.